Implikasi Kebijaksaan Salomo Bagi Guru Pendidikan Agama Kristen - Silsi Nadiati Saogo; Sozanolo Zamasi (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Wisdom is the right attitude in responding to every situation and event so that justice radiates. Wisdom is a decision that we take from the heart of conscience. Wisdom is also the nature and ability to use knowledge. Understanding of experience, common sense, and deep insight A wise person according to the Bible is one who is able to see life and God’s point of view and then know the best course of action to take A wise person is one who knows God’s hatt easy people will surely get respect and others, because you are not an easy thing people with attitude will not find easier to gain the truts of others because of the de honnati predicate.